Effect of Temperature and Catalyst Concentration on the Quality of Biodiesel Oil Extracted From Black Soldier Fly Larvae (Hermetia Illucens) - Dafit Ari Prasetyo; Aji Tri Nurlaeli; Haning Hasbiyati; Umi Sholikah; Zeni Ulma (Universitas Negeri Padang, 2025)
Biodiesel is a renewable and environmentally friendly energy source that can be produced from lipid-rich materials through the transesterification process. Black soldier fly (BSF) larvae (Hermetia Illucens) contain approximately 30–40% fat, making them a potential alternative feedstock for biodiesel production. This study aimed to evaluate the effect of reaction temperature and KOH catalyst concentration on the yield and quality of biodiesel derived from BSF larvae oil. Oil extraction was conducted using the Soxhlet method with n-hexane, where 15 g of dried larvae powder extracted for 240 minutes produced the highest oil yield of 97% (w/w). The extracted oil was then converted into biodiesel through transesterification at two temperatures (65°C and 70°C) and two catalyst concentrations (1% and 2% w/v KOH). Biodiesel quality was analyzed based on SNI 7182:2015. The highest biodiesel yield, 60.19% (v/v), was obtained at 70°C and 1% KOH (A2B1). The resulting biodiesel met major SNI requirements, including density (869.59 kg/m³), kinematic viscosity (4.75 cSt), cetane number (44.25), acid number (0.32 mg KOH/g), iodine number (16.8 g-I?/100 g), and FAME content (97.45%). These findings confirm that BSF larvae oil is a viable non-conventional feedstock for biodiesel production. This study is limited by the narrow range of reaction variables tested, suggesting that broader optimization—such as variations in alcohol ratio, reaction time, and pretreatment—may further improve yields. Practically, biodiesel production from BSF larvae supports waste valorization because larvae can be cultivated using organic waste streams. Socially, this approach reduces dependence on edible vegetable oils and supports circular economy initiatives. The originality of this research lies in its systematic evaluation of transesterification conditions for BSF-derived oil, providing new insights into the development of insect-based biodiesel technology.